The Influence of Information Technology Utilization, Information System Implementation and HR Competency on the Quality of Banjarmasin City Government Performance Reports - Agustina, Elvira; Hamdani*, Hamdani; Juniar, Asrid (Universitas Syiah Kuala, 2024)
This study aims to determine and analyze the effect of information technology utilization, implementation of Local Government Information Systems, and human resource competencies on the quality of Local Government Financial Reports on SKPD in Banjarmasin City. This type of research used is quantitative research. The research data was obtained by using a questionnaire distributed to financial management employees at SKPD in Banjarmasin City. The sampling were determined by using the purposive sampling. The analysis technique used is multiple linear analysis using the IBM SPSS Statistics application. The results of this study indicates that the utilization of information technology affects the quality of Local Government Financial Statements. Meanwhile, the implementation of Local Government Information Systems, and the competence of human resources does not effect the quality of Regional Government Financial Reports